Lantaden XR Glikosida dari Daun Lantana camara L. - Rumondang Bulan; Soekeni Soedigdo; Sadijah Achmad; Buchari Buchari (Jurnal Matematika & Sains, 2004)
Isolation and purification of lantadene XR glycoside compound related to lantadene compound, from Lantana camara L. leaves had been done. Structure elucidation was performed by interpretation of spectroscopic data, including UV, IR, MS, 1H and 13C-NMR. This compound is cytotoxic against of L1210 leukemic cell with IC50 of 2.23 Î¼g/mL.